Diffuse light and wetting differentially affect tropical tree leaf photosynthesis. Issue 1 (18th September 2019) - Berry, Z. Carter; Goldsmith, Gregory R.
Summary: Most ecosystems experience frequent cloud cover resulting in light that is predominantly diffuse rather than direct. Moreover, these cloudy conditions are often accompanied by rain that results in wet leaf surfaces. Despite this, our understanding of photosynthesis is built upon measurements made on dry leaves experiencing direct light. Using a modified gas exchange setup, we measured the effects of diffuse light and leaf wetting on photosynthesis in canopy species from a tropical montane cloud forest. We demonstrate significant variation in species‐level response to light quality independent of light intensity. Some species demonstrated 100% higher rates of photosynthesis in diffuse light, and others had 15% greater photosynthesis in direct light. Even at lower light intensities, diffuse light photosynthesis was equal to that under direct light conditions. Leaf wetting generally led to decreased photosynthesis, particularly when the leaf surface with stomata became wet; however, there was significant variation across species. Ultimately, we demonstrate that ecosystem photosynthesis is significantly altered in response to environmental conditions that are ubiquitous. Our results help to explain the observation that net ecosystem exchange can increase in cloudy conditions and can improve the representation of these processes in Earth systems models under projected scenarios of global climate change.